Creativity of Junior High School Students in Solving Problems Viewed From Cognitive Style - Abdul Rachman Taufik; Irmawaty Natsir; Dian Mayasari (Technium Social Sciences Journal, 2023)
Creative thinking is the ability of every individual to process information to build new ideas that are born from encouragement from themselves and their environment. The research objective was to determine the creativity of reflective students (S-R) and impulsive students (S-I) in solving open ended questions. The indicators used to measure student creativity are fluency, flexibility, and originality. The subjects that were targeted in this study were students who were at the VIII grade level of junior high school. The data collection method used was the MFFT (Matching Familiar Figure Test), written tests, and interviews. To categorize students into reflective and impulsive cognitive styles using the MFFT test, while to reveal students’ creativity in solving problems using a written test. The results of this study explain that reflective students (S-R) have a level of creative thinking at level 4, namely the very creative category (fluency, flexibility, and originality). While impulsive students (S-I) have a level of creative thinking at level 3, namely the creative category (fluency and flexibility). Reflective students in solving problems better than impulsive students.